The association between oral health and mild cognitive impairment in community-dwelling older adults - Ye, Niansi; Deng, Bei; Hu, Hui; Ai, Yating; Liu, Xueting; Zhou, Shi; Li, Yucan (Frontiers in Public Health, 2024)
Background: Older adults with cognitive impairment can experience poor oral health due to reduced self-care abilities, yet the impact of various oral health indicators on the cognitive abilities remains unclear. We investigated the relationship between oral health indicators and mild cognitive impairment (MCI) in older adults. Methods: A cross-sectional study of 234 older adults aged 65 years or over was performed form January to March 2023 in hospital. This study used the Mini-mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Activities of Daily Living (ADL), Clinical Dementia Rating (CDR) and Hachinski Ischemic Score (HIS) to measure MCI. Two qualified dentists performed clinical oral examinations (number of teeth, dental caries, removable dentures, periodontitis). The other oral health status was measured by subjective assessment questionnaires, and the oral health-related quality of life (OHRQoL) was assessed by Geriatric Oral Health Assessment Index (GOHAI).Results: Of the 234 older adults, 166 had MCI and 68 had normal cognitive ability. The univariate analyses revealed that older adults with poor oral health indicators of dental caries, chewing ability, oral and maxillofacial pain, self-perceived oral health, and OHRQoL had lower cognitive levels. The stepwise logistic regression analysis observed that higher literacy level (OR=0.064, 95%CI=0.007, 0.567) and OHRQoL score (OR=0.920, 95%CI=0.878, 0.963) were negatively associated with the presence of MCI. The area under the ROC curve (AUC) of MCI was 0.675 (95% CI: 0.600, 0.749) with a low sensitivity of 41.6% and a moderate specificity of 86.8%.Conclusions: OHRQoL was found to be associated with MCI, implying that OHRQoL may be important in cognitive decline. The GOHAI scale can be used to more easily assess the oral health of older adults, which is important for the timely detection of poor oral conditions to delay cognitive decline.